Kontribusi Prokrastinasi Akademik Terhadap Perilaku Game Addiction - Muhamad Disra Saputra; Marjohan Marjohan; Nevi Yarni S; Riska Ahmad (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2023)
This research is motivated by the high level of dependence on the use of the internet, especially as a medium of entertainment.Game online become one of the entertainment of various ages. Play Game online Too much can trigger the behavior game addiction. Academic procrastination or delay in learning is one of the effects of behavior game addiction the. This study aims to analyze the contribution of academic procrastination to behavior game addiction. This research uses a quantitative approach with a descriptive correlational type. The population of this study was faculty students at a university from various batches with a sample of 163 people, who were selected through a technique proportional stratified random sampling. The instrument used is a behavioral scale game addiction, academic procrastination scale with the Likert model. Research data were analyzed using a simple regression technique. The findings of this study indicate that student academic procrastination is in the moderate category, academic procrastination contributes significantly to student behavior.game addiction, The implications of the findings of this study can be used as input for creating a Guidance and Counseling service program at the university level.